HUBUNGAN KARAKTERISTIK SOSIAL EKONOMI TERHADAP ALOKASI PENGELUARAN WANITA KEPALA RUMAHTANGGA DI DAERAH ISTIMEWA YOGYAKARTA (Analisis Susenas Tahun 2005 dan 2010) - , FITRI ASTUTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
There are demographic factors that lead to women being a head of household like unmarried and set up their own household, take over responsibility of head household, divorce, overseas and the husband didnât make a living anymore. Several research reveal that women heads of households generally live in poverty. The percentage of women heads of household in DIY increase by 2005 and 2010 so itâs interesting to be studied. Besides the life expectancy of women who live in DIY is high so itâs getting more interesting. The aim of this research is to know the socio-economic characteristics of women heads of households by type of living area by 2005 and 2010. Moreover, this research is aimed to know the relationship of socio-economic characteristics of women heads of household to their household expenditure allocation in DIY by 2005 and 2010. This research used secondary data, which is Susenas DIY 2005 and 2010. Variables used in this research are a demographic, education, employment and economy. Analysis of the data used comparative analysis and contingency coefficient correlation. Based on study results, the urbanâs women head of household are young adults, unmarried, having small family, high educated, the main activities of working and schoolling, and having formal employment status by 2005 and 2010. The women head of household are living in rural areas tend to be elderly, divorce by dead, having small family, less educated, the main activities of working and taking care of the household, and having informal employment status. According to their household expenditure allocation, they live in urban areas tend to have not alimentary. While they live in rural areas tend to have alimentary expenditure. The number of household members is not related to the allocation of household expenditures. Educational level and employment status of women head of household are positively correlated with expenditure allocation. The higher level of education and employment status cause their household expenditure allocation tend to not alimentary.